Research on Multi-crane Cooperative Micro-motion Control of Combined Gantry Cranes for Turnout Laying and Replacement of High-speed Railways Based on Self-learning - LYU Maoyin; NIU Xuexin; CHEN Qishen; ZHAN Taiping (Kongzhi Yu Xinxi Jishu)
In view of bottlenecks encountered in the process of turnout laying and replacement on high-speed railways such as substantial construction difficulties, low efficiency, intensive labor workload, and high risk, this paper proposes a control method of intelligent turnout laying and replacement equipment with combined gantry cranes for high-speed railways. It is proposed to utilize a control strategy of asynchronous transverse movement and synchronous tilting of the combined gantry cranes to handle the rotation and longitudinal motion of large components respectively. A theoretical mathematical modeling analysis is performed for the turnout laying and replacement equipment with combined gantry cranes focusing on the rotation and longitudinal movement operations. Moreover, considering the flexible nature of chains in the real construction process of combined gantry cranes, a self-learning algorithm is incorporated to facilitate flexible and highly precise multi-crane cooperative micro-motion control. The experimental results from field operations showcases adopting the control method proposed in this article, stable and reliable rotation and longitudinal movement by the combined gantry cranes, with an operational error of less than 10 mm, achieving full compliance with the requirements of engineering applications demonstrates.